ANALYZING POLITICAL DISCOURSE IN THE MEDIA (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article explores the role of political discourse in the media, using discourse analysis to investigate how media outlets shape and influence public opinion. It discusses the methods employed, presents the results of the analysis, and offers a discussion on the implications of media discourse on politics, concluding with suggestions for more responsible and informed political communication.